Theoretical Studies for the Discovery of Potential Sucrase-Isomaltase Inhibitors from Maize Silk Phytochemicals: An Approach to Treatment of Type 2 Diabetes - Linda-Lucila Landeros-Martínez; Mara Ibeth Campos-Almazán; Nora-Aydeé Sánchez-Bojorge; Raul Flores; Juan Pedro Palomares-Báez; Luz María Rodríguez-Valdez (Molecules, 2023)
A theoretical analysis of the potential inhibition of human sucrase-isomaltase (SI) by flavonoids was carried out with the aim of identifying potential candidates for an alternative treatment of type 2 diabetes. Two compounds from maize silks, maysin and luteolin, were selected to be studied with the structure-based density functional theory (DFT), molecular docking (MDock), and molecular dynamics (MD) approaches. The docking score and MD simulations suggested that the compounds maysin and luteolin presented higher binding affinities in N-terminal sucrase-isomaltase (NtSI) than in C-terminal sucrase-isomaltase (CtSI). The reactivity parameters, such as chemical hardness (η) and chemical potential (µ), of the ligands, as well as of the active site amino acids of the NtSI, were calculated by the meta-GGA M06 functional in combination with the 6-31G(d) basis set. The lower value of chemical hardness calculated for the maysin molecule indicated that this might interact more easily with the active site of NtSI, in comparison with the values of the acarbose and luteolin structures. Additionally, a possible oxidative process was proposed through the quantum chemical calculations of the electronic charge transfer values (∆N) between the active site amino acids of the NtSI and the ligands. In addition, maysin displayed a higher ability to generate more oxidative damage in the NtSI active site. Our results suggest that maysin and luteolin can be used to develop novel α-glucosidase inhibitors via NtSI inhibition.